ANALISIS MANAJEMEN SEKURITI FISIK, KEAMANAN INDUSTRIAL, K3, MANAJEMEN RESIKO DAN IMPLEMENTASI SSMKD DI PT. EPSON INDONESIA - Jihan Salsabillah; Edy Soesanto, Abdul Maulana, Antonius Bimo Wicaksono (Adisam Publisher, 2024)
Physical security management is a precaution against loss of company assets for any reason. Industrial security is defined as safeguarding all company organizations to prevent the threat of crime and loss originating from outside or within the organization. K3 is a program created by workers and employers as an effort to prevent accidents. Risk management is identifying risks that have the potential to affect the company, and managing the risks. SSMKD is an important emergency management system for all areas of the company. This research uses a qualitative approach and data was obtained through literature studies of previous research. The aim of this research is to analyze the implementation of physical security management, industrial security, K3, risk management and the implementation of SSMKD at PT. Epson Indonesia. The method used in this research is literature study, namely by analyzing the results of previous research. The results of this research is PT. Epson has implemented physical security management, industrial security which includes K3, avoiding possible risks and implementing emergency management system standards. This can be seen from previous research which states that PT. Epson has installed security devices in the form of CCTV, a hydrant pipe system and built walls to maintain the company's security.